Steady-State Hydraulic Analysis of High-Rise Building Wastewater Drainage Networks: Modelling Basis - Colin Stewart; Michael Gormley; Yunpeng Xue; David Kelly; David Campbell (Buildings, 2021)
A model is presented which allows steady-state pressure profiles in high-rise wastewater drainage networks to be related to intake air flowrates and discharge water flowrates. This model is developed using data taken from academic literature, and is based on experimental observations which suggest that a vertical annular downflow develops over distance such that the pressure gradient in the wet stack may be expressed as the sum of junction components and developed flow components. The model is used to analyse a simplified ‘medium rise’ primary vented system of height 40 m, hosting two inflow junctions, crossvents and Air Admittance Valves (AAVs). The model illustrates how the air supply configuration affects the airflow rates within the stack and the vents, and how the configuration affects the steady-state hydraulic pressure profile. The model offers the possibility of an alternative approach to the design of high-rise wastewater drainage networks, compared to existing design codes. These codes generally do not explain the role that the air admitted into the network has upon its performance.